2015
DOI: 10.1136/archdischild-2013-305847
|View full text |Cite
|
Sign up to set email alerts
|

Country level economic disparities in child injury mortality

Abstract: BackgroundInjuries are a neglected cause of child mortality globally and the burden is unequally distributed in resource poor settings. The aim of this study is to explore the share and distribution of child injury mortality across country economic levels and the correlation between country economic level and injuries.MethodsAll-cause and injury mortality rates per 100 000 were extracted for 187 countries for the 1–4 age group and under 5s from the Global Burden of Disease Study 2010. Countries were grouped in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Deaths are then rescaled for each cause so that the sum equals the number of deaths from all causes to ensure internal consistency. YLLs were calculated by multiplying deaths by the residual life expectancy at the age of death based on the GBD 2017 standard model life table 12…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deaths are then rescaled for each cause so that the sum equals the number of deaths from all causes to ensure internal consistency. YLLs were calculated by multiplying deaths by the residual life expectancy at the age of death based on the GBD 2017 standard model life table 12…”
Section: Methodsmentioning
confidence: 99%
“…Up till now, few studies have been performed that studied the relationship between sociodemographic changes and overall injury rates. There have been reports on the associations of gross domestic product and unemployment with suicides, homicides, road injury and unintentional injuries 5–12. However, these studies focused on one specific cause of injury and on one type of injury outcome, mostly mortality.…”
Section: Introductionmentioning
confidence: 99%
“…This relationship has also been established in the injury field for children under five (Khan et al, 2015) and in the 1–19 age group globally (Peden et al, 2008). For child burns, 2004 data at the global level showed that mortality was nearly 11 times higher in low-income countries than in high-income countries (Peden et al, 2008).…”
Section: Introductionmentioning
confidence: 78%
“…Increased risk of severe injuries related to poverty (for those with worsening income opportunities); reduction in parental supervision; increase in affluence leads to exposure to risk from unsafe operations of newly acquired product/devices 4 Several studies have shown that low socioeconomic status is strongly associated with child unintentional injuries, 4,20,22 and that most child unintentional injuries occur within in home settings. 4 Hence, improving living wages for families who participate in the manufacture of goods and services intended for globalized markets would impact living conditions and potentially reduce the risk of child unintentional injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is a correlation between economic development and increase in proportionate mortality from child unintentional injuries. 20 This correlation is driven in part by the forces of globalization maintained by complex international laws that increase labor and free market access, which disproportionately shifts economic gains and risk factors of child unintentional injuries between the HIC and LMIC. Recognizing the growing inequalities in the benefits of globalization between HIC and LMIC is at the crux of understanding pathways for leveraging globalization to reduce deaths and morbidity from child unintentional injuries.…”
Section: Discussionmentioning
confidence: 99%